Hematological Effects of Gold Nanorods on Erythrocytes: Hemolysis and Hemoglobin Conformational and Functional Changes. Issue 12 (25th September 2017) - Zhao, Xingchen; Lu, Dawei; Liu, Qian S.; Li, Yiling; Feng, Rui; Hao, Fang; Qu, Guangbo; Zhou, Qunfang; Jiang, Guibin
Abstract: Gold nanorods (GNRs) are a unique class of metal nanostructures that have attractive potentials in biomedical applications, and the concern on their biological safety is concomitantly increasing. Hemocompatibility is extremely important as their contact with blood circulation is unavoidable during in vivo delivery. Herein, two kinds of GNRs coated with hexadecyltrimethylammonium bromide (C‐GNRs) or poly(sodium‐ p ‐styrenesulfonate) are used to test their potential toxicological effects in blood. C‐GNRs with positive surface charges efficiently induce hemolysis when encountering erythrocytes. Cellular internalization of C‐GNRs is found, and they subsequently bind with hemoglobin, forming bioconjugates. The interaction between hemoglobin and C‐GNR (stoichiometry 32.7:1) is regulated by electrostatic forces. Chromophores like tryptophan (Trp) are found to interact with C‐GNRs, causing enhancement in fluorescence intensity. The conformation of protein is partially altered, evidenced by decrease in α‐helical, increase in β‐sheet and random coil of hemoglobin. Although C‐GNRs do not essentially decrease oxygen binding capacity of hemoglobin, they hamper oxygen release from the protein. Heme, the oxygen binding unit, releases from hemoglobin upon C‐GNR treatment, which could contribute to C‐GNR‐induced hemolysis. This study demonstrates the hematological effects of GNRs, revealing their potential risk in biomedical applications. Abstract : The hematological effects are investigated for positively charged gold nanorods (C‐GNRs) and negatively charged ones (P‐GNRs). In contrast to P‐GNRs, C‐GNRs efficiently induce hemolysis when encountering erythrocytes. C‐GNRs subsequently bind with hemoglobin after being encapsulated, inducing conformational and functional changes of the protein. The bound hemoglobin partially loses its function of oxygen release while retaining the oxygen binding capacity.